The effect of quercetin on cerulein-induced acute pancreatitis - Kahraman,Ahmet (2017)
OBJECTIVE: The aim of this study was to evaluate the protective and therapeutic effects of quercetin on pancreatic injury in cerulein-induced acute pancreatitis. METHOD: Thirty-two rats were randomly divided into four groups, eight per group: (CT): untreated controls, (CER) treated with cerulein, 50 µg/kg body weight; (Q+CER) pre-treatment with quercetin, 100 mg/kg body weight, followed by cerulein, 50 µg/kg; (CER+Q) post-treatment, cerulein followed by quercetin, same doses. Cerulein was divided into four doses, given at 1-hour intervals by intraperitoneal injection. Quercetin was given either 1-hour before (in pre-treatment group) or 1-hour after (in post-treatment group) cerulein. Pancreatic malondialdehyde (MDA), carbonyl, myeloperoxidase (MPO), tumor necrosis factor-alpha (TNF-a), interleukin-6 (IL-6), reduced and oxidized glutathione (GSH and GSSG, respectively) were measured. Histology of the pancreas was studied. RESULTS: (1) MDA, carbonyl, MPO, TNF-a and IL-6 levels were significantly higher in CER vs CT rats. (2) MDA, carbonyl, MPO and TNF-α decreased significantly in pre-treated rats vs. CER. (3) MDA, MPO, TNF-α, IL-6 were significantly lower in post-treated rats vs. CER. (4) The reduced vs. oxidized glutathione ratio (GSH/GSSG) of was significantly lower CER vs. CT rats. (5) Pre- and post-treatment with quercetin significantly increased this ratio. (6) Pancreatic histology showed that quercetin had no significant effect on the histological image of the pâncreas CONCLUSION: These results suggest that quercetin can attenuate the severity of cerulein-induced acute pancreatitis by acting as an antioxidant and anti-inflammatory agent and combating oxidative stress. Further studies are needed to clearly explain its utility on acute pancreatitis.